Currículo Integrador na Educação Infantil: concepção e visão de educadores do ensino municipal da cidade de São Paulo - Nascimento, Fabiana Borelli Gomes do (2018)
This dissertation aims to analyze the principles and conceptions of the Integrative Curriculum from the perspective of a group of educators, focusing on the subsidies of the document "Curriculum Integrator of Childhood Paulistana", promoted by the Municipal Education Department of São Paulo. The study delimited the research scenario in an Educational Unit of Early Childhood Education in the District of Cidade Tiradentes and used the qualitative methodology (ANDRÉ, 2000; GAMBOA, 2000; CHIZZOTTI, 2003) to support the research. We constructed an open questionnaire (GIL, 2008), as an instrument for data collection, with the intention of revealing how the teachers understand the Integrative Curriculum and how these conceptions are embedded in their actions. The most problematized themes were highlighted and analyzed in consonance with specific theoretical literature. We found in the teachers' statements, elements indispensable to integrative pedagogical practices, such as the organization of times, spaces and materials, play, the integration of knowledge of different curricular components, children's cultures and protagonism. We perceive from the reflections carried out, an involvement of the educators, in approaching the foundations of the "Integrative Curriculum" the educational practices, for that, we emphasize the formative process, the discussions of the educational routines, as a field of strengthening and deepening to the integrative conceptions, in respect to childhood